1996
DOI: 10.3109/01421599609034145
|View full text |Cite
|
Sign up to set email alerts
|

Medical students and people with disabilities: A teaching unit tor medical students exploring the impact of disability on the individual and the family

Abstract: This paper describes an innovative teaching unit developed by staff at Monash University, Australia. The unit was designed to give jirst-year medical students insight into the impact of a developmental disability on an individual and hidher family. The students were given opportunities to learn directly from people with disabilities, their families and professionals working with them in the community about their health, educational and social needs. The teaching unit was well received by the students and pre-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Results suggested that the students were more comfortable interacting with people with disabilities after the intervention, with 77% of students valuing the opportunity to meet people with disabilities during the intervention. However, as with Tracy and Graves (1996), these findings are difficult to interpret due to the measure's lack of specificity. Andrew, Siegel, Politch, and Coulter (1998) also used a generic measure of attitudes to those with disabilities in their evaluation of training, which included experiences with children with developmental disabilities.…”
Section: Research Suggesting Improved Attitudes: Generic Measuresmentioning
confidence: 88%
See 2 more Smart Citations
“…Results suggested that the students were more comfortable interacting with people with disabilities after the intervention, with 77% of students valuing the opportunity to meet people with disabilities during the intervention. However, as with Tracy and Graves (1996), these findings are difficult to interpret due to the measure's lack of specificity. Andrew, Siegel, Politch, and Coulter (1998) also used a generic measure of attitudes to those with disabilities in their evaluation of training, which included experiences with children with developmental disabilities.…”
Section: Research Suggesting Improved Attitudes: Generic Measuresmentioning
confidence: 88%
“…Studies that used measures of attitudes towards persons with disabilities in general also suggested that ID teaching/training enhanced medical students' attitudes (e.g., Tracy & Graves, 1996;Tracy & Iacono, 2008). However, such measurement is problematic as scales non-specific to ID may omit critical aspects of students' attitudes towards this clinical group.…”
Section: Research Suggesting Improved Attitudes: Generic Measuresmentioning
confidence: 93%
See 1 more Smart Citation
“…The knowledge gap of health practitioners within the field of disability has been recognised by those teaching in universities and attempted to be addressed with the development of innovative models of interprofessional curriculum. For example, guest "tutors" with disability (Tracy & Graves, 1996), "real-life" DVD scenarios (Iacono et al, 2011), and semester-long integrated programs of content (Morgan & Lo, 2013) have been trialled in a range of health professional training programs. However, targeted employment opportunities with structured mentoring and skill development within the disability sector remain limited, resulting in some generic health practitioners providing services for adults with CP (Bent et al, 2002;Ng et al, 2003;Nieuwenhuijsen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Also available are studies on the attitudes of medical students towards persons with intellectual disabilities [1114]. Research on attitudes towards the sexuality of persons with intellectual disabilities, including students of obstetrics as participants [15], nurses employed as caring staff at institutions for disabled persons [16], personnel who work with intellectually disabled persons within the scope of their professional competences (nurses, physiotherapists, general practitioners) of various forms [1719], addressed several issues within the broadly understood area of sexuality of persons with intellectual disabilities.…”
Section: Introductionmentioning
confidence: 99%